Sensitivity studies for the IceCube-Gen2 radio array - The IceCube Gen2 Collaboration; Hallmann, Steffen; Abbasi, Rasha; Ackermann, Markus; Adams, Jenni; Aguilar, Juanan; Ahlers, M.; Ahrens, Maryon; Alispach, Cyril Martin; Allison, Patrick; Alves Junior, Antonio Augusto; Amin, Najia Moureen Binte; et al. (Scuola Internazionale Superiore di Studi Avanzati, 2021)
The IceCube Neutrino Observatory at the South Pole has measured the diffuse astrophysical neutrino flux up to ∼PeV energies and is starting to identify first point source candidates. The next generation facility, IceCube-Gen2, aims at extending the accessible energy range to EeV in order to measure the continuation of the astrophysical spectrum, to identify neutrino sources, and to search for a cosmogenic neutrino flux. As part of IceCube-Gen2, a radio array is foreseen that is sensitive to detect Askaryan emission of neutrinos beyond ∼30 PeV. Surface and deep antenna stations have different benefits in terms of effective area, resolution, and the capability to reject backgrounds from cosmic-ray air showers and may be combined to reach the best sensitivity. The optimal detector configuration is still to be identified.